LPS-Induced Inflammation Potentiates the IL-1-Mediated Reduction of LH Secretion from the Anterior Pituitary Explants - Andrzej Przemysław Herman; Agata Krawczyńska; Joanna Bochenek; Elżbieta Dobek; Anna Herman; Dorota Tomaszewska-Zaremba (Clinical and Developmental Immunology)
Acting at the level of the brain, interleukin- (IL-)1β is considered to be one of the most potent downregulators of reproduction processes during immune/inflammatory challenge. IL-1β suppresses gonadotropin-releasing hormone (GnRH) secretion from the hypothalamus resulting in the inhibition of the luteinizing hormone (LH) release from the anterior pituitary (AP). However, the presence of IL-1β receptors in the AP suggests the possible direct action of this cytokine on LH secretion. The study was designed to determine the effect of IL-1β on the LH secretion from the AP explants collected from saline and LPS-treated ewes in the follicular phase. It was found that IL-1β suppressed () GnRH-stimulated LH release and LHβ gene expression in AP explants in both groups. However, IL-1β action was more potent in the explants collected from LPS-treated animals. Pituitaries from LPS-treated animals were characterized by increased () IL-1 type I receptor and decreased () GnRH receptor gene expression level compared to the saline-treated group. IL-1β also affected the GnRH-R gene expression in explants collected from LPS-treated animals. Our results show that direct action of IL-1β on the pituitary gonadotropes could be one of the reasons of the reproductive processes disorders accompanying an inflammatory state.